Reprint of: Development of bioactive peptide amphiphiles for therapeutic cell delivery. (1st September 2015) - Webber, Matthew J.; Tongers, Jörn; Renault, Marie-Ange; Roncalli, Jerome G.; Losordo, Douglas W.; Stupp, Samuel I.
Abstract: There is great clinical interest in cell-based therapies for ischemic tissue repair in cardiovascular disease. However, the regenerative potential of these therapies is limited due to poor cell viability and minimal retention following application. We report here the development of bioactive peptide amphiphile nanofibers displaying the fibronectin-derived RGDS cell adhesion epitope as a scaffold for therapeutic delivery of bone marrow derived stem and progenitor cells. When grown on flat substrates, a binary peptide amphiphile system consisting of 10 wt.% RGDS-containing molecules and 90 wt.% negatively charged diluent molecules was found to promote optimal cell adhesion. This binary system enhanced adhesion 1.4-fold relative to substrates composed of only the non-bioactive diluent. Additionally, no enhancement was found upon scrambling the epitope and adhesion was no longer enhanced upon adding soluble RGDS to the cell media, indicating RGDS-specific adhesion. When encapsulated within self-assembled scaffolds of the binary RGDS nanofibers in vitro, cells were found to be viable and proliferative, increasing in number by 5.5 times after only 5 days, an effect again lost upon adding soluble RGDS. Cells encapsulated within a non-bioactive scaffold and those within a binary scaffold with scrambled epitope showed minimal viability and no proliferation. Cells encapsulated within this RGDS nanofiber gel also increase in endothelial character, evident by a decrease in the expression of CD34 paired with an increase in the expression of endothelial-specific markers VE-Cadherin, VEGFR2 and eNOS after 5 days. In an in vivo study, nanofibers and luciferase-expressing cells were co-injected subcutaneously in a mouse model. The binary RGDS material supported these cells in vivo, evident by a 3.2-fold increase in bioluminescent signal attributable to viable cells; this suggests the material has an anti-apoptotic and/or proliferative effect on the transplanted bone marrow cells. We conclude that the binary RGDS-presenting nanofibers developed here demonstrate enhanced viability, proliferation and adhesion of associated bone marrow derived stem and progenitor cells. This study suggests potential for this material as a scaffold to overcome current limitations of stem cell therapies for ischemic diseases.